STUDY OF INFLUENCE OF SOME ADDITIVES ON THE RATE OF CUMENE AUTOXIDATION: II. INFLUENCE OF UNSATURATED CYANO-LACTON AND DIMETHYL SULFOXIDE (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
The influence of 2-cyano-3,4,4-trimethyl-2-butene-4-olyd (unsaturated cyanolactone, UCL) and DMSO on the rate of initiated with AIBN of cumene (CU) autoxidation in chlorobenzene solution by gasometric method is studied. It is established that in the presence of UCL (for reaction order n=0.6) the stationary reaction rate Rst can be described by empirical rate law. In the case of DMSO (n=0.5) a classical rate law of radical-chain reactions in the stationary regime is occurring. In both cases the reaction begins after some induction period, τ. With increasing of [UCL]0 τ is decreasing up to 0, when [UCL]0$≥ 2·$10-3 M. It is shown also that DMSO decreases Rst, which, probably, can be explained by DMSO and CU competition to react with ROO• free radicals, which are being formed in the reaction propagation step.
Keywords: cumene autoxidation, radical reactions, unsaturated cyano-lacton, DMSO as antioxidator